Novel CNS glutamate receptor subunit genes of Drosophila melanogaster. - Volkner, M.; Lenz-Bohme, B.; Betz, H.; Schmitt, B. (Journal of Neurochemistry, 2000)
We report the identification and characterization of two genes from Drosophila melanogaster that encode novel ionotropic glutamate receptor proteins, named DGluR-IB and DNMDAR-II, and that are located on chromosome 3L, region 67AB, and the X chromosome, position 2B, respectively. The DGluR-IB full-length cDNA was isolated from Drosophila embryonic and head libraries. The encoded protein of 1,095 amino acids displays high sequence identity (73%) to DGluR-IA. The DNMDAR-II gene was identified by sequence-homology searches in databases. The deduced protein shows moderate sequence identity (29-31%) to the mouse NMDAR2A-D receptor subunits. Whole-mount in situ hybridization on embryos revealed DGluR-IB and DNMDAR-II transcripts in the CNS. Immunofluorescence analysis of the adult fly brain indicates that the DGluR-IB protein is expressed in neurons implicated in the regulation of the circadian clock.